Genome-Wide Analysis of the Soybean TIFY Family and Identification of GmTIFY10e and GmTIFY10g Response to Salt Stress - Liu, Ya-Li; Zheng, Lei; Jin, Long-Guo; Liu, Yuan-Xia; Kong, Ya-Nan; Wang, Yi-Xuan; Yu, Tai-Fei; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Wang, Feng-Zhi; Ma, You-Zhi; et al. (Frontiers in Plant Science, 2022)
TIFY proteins play crucial roles in plant abiotic and biotic stress responses. Our transcriptome data revealed several TIFY family genes with significantly upregulated expression under drought, salt, and ABA treatments. However, the functions of the GmTIFY family genes are still unknown in abiotic stresses. We identified 38 GmTIFY genes and found that TIFY10 homologous genes have the most duplication events, higher selection pressure, and more obvious response to abiotic stresses compared with other homologous genes. Expression pattern analysis showed that GmTIFY10e and GmTIFY10g genes were significantly induced by salt stress. Under salt stress, GmTIFY10e and GmTIFY10g transgenic Arabidopsis plants showed higher root lengths and fresh weights and had significantly better growth than the wild type (WT). In addition, overexpression of GmTIFY10e and GmTIFY10g genes in soybean improved salt tolerance by increasing the PRO, POD, and CAT contents and decreasing the MDA content; on the contrary, RNA interference plants showed sensitivity to salt stress. Overexpression of GmTIFY10e and GmTIFY10g in Arabidopsis and soybean could improve the salt tolerance of plants, while the RNAi of GmTIFY10e and GmTIFY10g significantly increased sensitivity to salt stress in soybean. Further analysis demonstrated that GmTIFY10e and GmTIFY10g genes changed the expression levels of genes related to the ABA signal pathway, including GmSnRK2, GmPP2C, GmMYC2, GmCAT1, and GmPOD. This study provides a basis for comprehensive analysis of the role of soybean TIFY genes in stress response in the future.